OPTIMAL TIMING AND METHODS FOR ASSESSING THE CONDITION OF THE UTERINE SCAR AFTER CESAREAN SECTION - Kurbaniyazova V. E. (The Conference Hub, 2025)
The increasing frequency of cesarean sections in recent years has raised concerns about the assessment of uterine scar integrity, as its condition directly affects the feasibility of subsequent vaginal delivery, the risk of uterine rupture, and abnormal placentation. Determining the optimal timing for diagnosis and selecting the most informative assessment methods are crucial for patient management. Standard ultrasound techniques do not always provide a complete picture of scar status; therefore, the use of advanced technologies such as 3D ultrasound, elastography, magnetic resonance imaging (MRI), and hysteroscopy enables a more precise evaluation of structural integrity, functional viability, and the risk of complications.